An Analysis of Outpatients’ Perceived Service Quality and Satisfaction in Selected Private Hospitals of Kathmandu - Pathak, Paridhi (Journal of Business and Social Sciences Research, 2018)
Patients’ perceptions about health services, especially about service quality, are becoming increasingly important. It might shape confidence and subsequent behaviors with regard to their choice and usage of the available health care facilities. The study examines the primary satisfaction with a private hospital experience and estimate the effect that each of these construct will have on future behavioral intensions. More specifically, it measures patient’s perceptions of service quality and assesses the dimensions of service quality exert strongest influence on customer satisfaction. The study is based on primary data, which collected from outpatients in the ten selected private hospitals of Kathmandu valley via self-administered and structured questionnaire survey. Convenience sampling method is applied for the study that constituted of 200 outpatients from private hospitals. The present study is based on the SERVPREF model in which independent variables are tangibles, responsiveness, empathy, reliability and assurance whereas the dependent variable is overall satisfaction of the patients. The findings of this study show that 72 percent of the respondents are satisfied with the overall quality of the hospitals; 5 percent are dissatisfied and 18 percent are neutral. It also reveals that satisfaction of the outpatients is irrespective of their genders, age, income level and education. Among all constructs the most positive perceptions are seen in the assurance dimension of the hospitals followed by tangibles, responsiveness, reliability and empathy. Additionally, it is seen that responsiveness dimension is the most strongly correlated dimension with overall satisfaction; while the other dimensions have weak to moderate positive correlation. Overall, a positive relationship is found between patient’s perception of service quality and their satisfaction. Journal of Business and Social Sciences Research, Vol. 2, No. 1 & 2, pp. 69-84